A model of cognitive and operational memory of organizations in changing worlds - Giovanni Dosi; Luigi Marengo; Evita Paraskevopoulou; Marco Valente (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This work analyzes and models the nature and dynamics of organizational memory, as such an essential ingredient of organizational capabilities. There are two sides to it, namely a cognitive side, involving the beliefs and interpretative frameworks by which the organization categorizes the states of the world and its own internal states, and an operational one, including routines and procedures that store the knowledge of how to do things. We formalize both types of memory by means of evolving systems of condition-action rules and investigate their performance in different environments characterized by varying degrees of complexity and non-stationarity. Broadly speaking, in simple and stable environments memory does not matter, provided it satisfies some minimal requirements. In more complex and gradually changing ones more memory is better. However there is some critical level of environmental instability above which forgetfulness is evolutionary superior from the point of view of long term performance. Moreover, above some (modest) complexity threshold stable and robust cognitive categorizations and routinized behavior emerge.
Keywords: C12; C13; C46; C52; R12; 330; organizational memory; routines; cognitive categories; condition-action rules